Biopolymers to mitigate the environmental impact - Montecinos Espinoza, Susana de Los Angeles (2019)
The aim of this work was to show some possible solutions to the environmental pollution due to the plastic problem. The strategy was to presentsome alternatives that, to our understanding, are more likely to be appliedin a near future. The use of biodegradable polymers coming from natural sources or agricultural waste was developed by means of three examples: starch, PLA and PHA. On the other hand,the possibility of fabricate green polymers was briefly developed. PLA exhibits the greatest current development, while starch has the advantage of its low cost. PHA, mainly PHB, has good chances of replacing some synthetic polymers if its mechanical properties are improved.